KNOWLEDGE MANAGEMENT AND FIRM PERFORMANCE IN SMEs: THE ROLE OF SOCIAL CAPITAL AS A MEDIATING VARIABLE - Salina Daud,; Wan Fadzilah Wan Yusoff, (Asian Academy of Management Journal, 2010)
Knowledge and intellectual capital are increasingly recognised as the main sources of competitive advantages in the knowledge-based economy. Businesses, particularly those that are small- or medium-sized, find that they need to give increasing attention to knowledge management and social capital — social capital being a mediating variable between knowledge management processes and firm performance. This study examined knowledge management, social capital and firm performance through the use of a questionnaire directed to small- and medium-sized enterprises — all of them situated within the Multimedia Super Corridor in the Klang Valley of Malaysia. The results based on 289 usable questionnaires demonstrated the following: (i) knowledge management processes influence social capital positively; (ii) social capital enhances firm performance; and (iii) social capital is a mediator between knowledge management processes and firm performance. The research demonstrated that knowledge management processes and social capital can be integrated to enhance firm performance.